2019
DOI: 10.4103/jfmpc.jfmpc_597_19
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of domestic violence and its socio-demographic correlates among pregnant women in Delhi

Abstract: Context:Domestic violence is violation of basic human rights, and poses a threat to the physical, mental, and social health aspects of women and her children. The causation of domestic violence is precipitated by many risk factors.Aims:Aim was to estimate the magnitude of domestic violence overall, and its sub-types, among pregnant women. The study also aimed to find the associated socio-demographic determinants of domestic violence among the subjects.Settings and Design:The study was designed as a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Only six studies investigated bidirectionality of IPV. In the studies focused on bidirectional IPV, two of these studies were during pregnancy ( 37 , 89 ), one study was during the postpartum period ( 46 ), and three studies were during both pregnancy and the postpartum period ( 42 , 58 , 66 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only six studies investigated bidirectionality of IPV. In the studies focused on bidirectional IPV, two of these studies were during pregnancy ( 37 , 89 ), one study was during the postpartum period ( 46 ), and three studies were during both pregnancy and the postpartum period ( 42 , 58 , 66 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…At follow-up (i.e., during postpartum), a range between 12.3 and 54.1% of women endorsed at least one instance of IPV victimization and 7.4–64.8% endorsed at least one instance of IPV perpetration. After childbirth, two studies suggest that prevalence of IPV perpetration declined for about 10% ( 58 , 66 ), whereas Charles & Perreira ( 41 ) reported around 20% increase in prevalence ( 42 ). In regard to IPV victimization, only Hellmuth et al ( 66 ) reported around 10% increase in prevalence estimates, while others suggest a decrease in prevalence rates for <20% ( 42 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] where the prevalence of Verbal violence was found to be 86.1% followed by physical violence in 63.4% and Garg et al . [ 14 ] who also found that verbal violence followed by economical violence was mainly present. In a study done by Jeyaseelan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Caste, religion, literacy status of study subjects, and occupational status of spouses of study subjects were reported as significant correlates affecting the causation of domestic violence among the subjects. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%